Veer10-acht10 : de leefwereld van jongeren - Allegaert, Patrick; Van Bouchaute, Bart (Leuven : Garant, 1999)
BMLIK
Vlaams Welzijnscongres over/met jongeren 18 en 19 februari 199 te Kortrijk.
Nederlands
Monografie
Keywords: jongeren